Frey syndrome following herpes zoster in an otherwise healthy girl. (25th July 2018) - Guri, Alex; Scheier, Eric; Garty, Yael
Abstract : A 12-year-old girl presented with red spots appearing on the left side of her face. The girl was usually healthy and fully vaccinated, including varicella vaccination. Six years prior to her presentation, she had suffered an episode of blister rash on the left side of her face, including lesions in the ear canal and buccal mucous membrane. A diagnosis of herpes zoster was made, and she was treated with acyclovir with complete skin recovery. A hearing examination demonstrated mild-to-moderate left neurosensory hearing loss. Since then, she is having short episodes of redness on her face without pain or sweating at the exact distribution of the zoster blisters 6 years ago. The appearance of spots is related to sour foods, such as sour flavoured candies, yoghourt and green apples. The diagnosis of postherpetic Frey syndrome was made, and observational approach was adopted due to the benign character of symptoms.